2016
DOI: 10.1787/5jlnb59ll80x-en
|View full text |Cite
|
Sign up to set email alerts
|

How OECD health systems define the range of good and services to be financed collectively

Abstract: systems/health-working-papers.htm OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcomed, and may be sent to health.contact@oecd.org. This series is designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…Health technology assessment (HTA) can complement the use of evidence-based clinical guidelines by providing evidence related to new medical technologies during assessment, appraisal and decision-making processes (Auraaen et al 2016;OECD 2010;Mossialos and Le Grand 1999). Criteria for investment and disinvestment decisionmaking sit within the broader context of activities aimed at encouraging best practices in health care, and may include results from HTA examining the clinical and economic evaluation of new technologies.…”
mentioning
confidence: 99%
“…Health technology assessment (HTA) can complement the use of evidence-based clinical guidelines by providing evidence related to new medical technologies during assessment, appraisal and decision-making processes (Auraaen et al 2016;OECD 2010;Mossialos and Le Grand 1999). Criteria for investment and disinvestment decisionmaking sit within the broader context of activities aimed at encouraging best practices in health care, and may include results from HTA examining the clinical and economic evaluation of new technologies.…”
mentioning
confidence: 99%
“…Social protection in India has evolved into a complex system characterised by low coverage, inadequate benefits, fragmentation and a lack of co-ordination across agencies (Asher, Zen and Dita, 2018 [69]). The federal structure in India implies that the design and implementation of social protection programmes is shared between different levels of government, 2 with the union typically designing programmes while the states implement them, and the states may complement those with state-specific programmes.…”
Section: Social Protection In Indiamentioning
confidence: 99%
“…).The National Social Security System (Sistem Jaminan Sosial Nasional; SJSN) Law No. 40 of 2004 mandates universal coverage of social security for all Indonesians, including healthcare, work accident, old-age savings, pension and death (Asher, Zen and Dita, 2018[69]). The SJSN was formulated in 2004 but first implemented in 2014, after the passing of 2011 Social Security Provider Law No.…”
mentioning
confidence: 99%
“…Hofmarcher et al (2019 [4]) estimated that in all European countries, the five-year survival rates increased for most common cancer types between 1995 and 2014. Within this same period, Arnold et al (2019 [6]) found that five-year net survival increased in almost all of seven cancer types in seven high-income countries (Australia, Canada, Denmark, Ireland, New Zealand, Norway and the United Kingdom). The highest observed increases in five-year survival were 16.6 and 21.0 percentage points for colorectal cancer in Denmark in the periods 1995-1999 and 2010-2014, respectively (Arnold et al, 2019 [6]).…”
mentioning
confidence: 95%